Implementation and Change of Processual Administrative Legislation Through an Innovative Web 2.0 Solution - Polona KOVAČ; Mitja DEČMAN (Transylvanian Review of Administrative Sciences, 2009)
Various extensive public sector reforms have been carried out across the world with the clear aim of making the services concerned more efficient and responsive to the needs of their users, such as the citizens, political authorities, and administrative bodies covering other public administration fields. The ever advancing information technology has frequently been used to support such reforms. Over the last years, the public phenomenon of Web 2.0 has even attracted some attention within e-government because of its vast success in the general civic environment. The paper investigates the possibilities of implementing such a Web 2.0 solution for the case of application of legislation and management of changes made into it through the example of the Slovenian General Administrative Procedure Act – a law that is subsidiarily used by practically all administrative bodies and therefore has to be applied in different fields, coping with sectoral legislation more or less coherent with it. To present the potential, patterns and risks (such as the limited role of public administration in interpreting law) of such activities of using Web 2.0, the paper employs theory research, actual cases from different segments of the public sector, and a real example of a solution currently in the beta stage of development – the so-called Administrative Consultation Wiki, a project run by the Slovenian Faculty of Administration and the Ministry of Public Administration of the Republic of Slovenia. The findings suggest a major potential of this kind of solutions, and point to the possibilities as well as warn of the risks involved.